Preparation method of composite silicon-based negative pole piece for solid-state lithium ion battery

By using a composite preparation method of micron-scale silicon and nano-scale silicon in lithium-ion batteries, composite silicon-based negative electrode sheets are prepared, which solves the problem of powdering and falling off of silicon-based negative electrode materials during charging and discharging, achieves higher cycle stability and rate performance, and improves the overall energy density and reliability of the battery.

CN119601605AActive Publication Date: 2025-03-11SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510137856.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-11
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

The silicon-based negative electrode material in lithium-ion batteries is prone to material powdering and active substances falling off after multiple charges and discharges, resulting in the cycle life that cannot meet the requirements of commercial applications.

Method used

Using the composite preparation method of micron-scale silicon particles and nano-scale silicon particles, by screening and mixing silicon particles with different particle sizes to form composite silicon components, and mixing them with conductive carbon black, functional fillers and binders in polar solvents, a negative electrode slurry is prepared, and a composite silicon-based negative electrode sheet is obtained by vacuum curing.

Benefits of technology

Through the reasonable proportion of micron silicon and nano-silicon, the volume changes are buffered, structural damage is reduced, the cycle stability and rate performance of the battery are improved, and the overall energy density and use reliability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601605A_ABST
    Figure CN119601605A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite silicon-based negative pole piece for a solid-state lithium ion battery, which comprises the following steps: screening micron-sized silicon particles and nano-sized silicon particles, and mixing the micron-sized silicon particles and the nano-sized silicon particles according to the weight ratio of (40-95): (5-60) to obtain a composite silicon component; mixing the composite silicon component, conductive carbon black, a functional filler and a binder in a polar solvent to obtain negative electrode slurry; and coating the negative electrode slurry on a negative electrode current collector, and carrying out vacuum curing to obtain the composite silicon-based negative electrode plate. According to the preparation method, the advantage of high capacity of a silicon material can be played, the problem of electrode failure caused by volume expansion of silicon is solved to a certain extent, higher specific capacity, longer cycle life and better rate capability are brought to the lithium ion battery, and the overall energy density and the use reliability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor device production, and in particular relates to a method for preparing a composite substrate for semiconductor device production. Background Art

[0002] Since its commercialization in the 1990s, lithium-ion batteries have been widely used in consumer electronics, electric vehicles, energy storage and other fields due to their high energy density and no memory effect. Currently, most lithium-ion batteries use graphite as the negative electrode material, but its low theoretical capacity (about 372 mAh / g) restricts the further development of lithium-ion batteries. As commercial graphite negative electrode lithium-ion batteries have gradually approached their ultimate energy density, it is urgent to find negative electrode materials with higher capacity. Silicon (Si) is considered to be one of the most promising potential anode materials for lithium-ion batteries in practical applications due to its low working potential (<0.5 V vs Li / Li+) and high theoretical specific capacity (4200 mAh / g). However, the low intrinsic electronic conductivity of silicon anode and the large volume effect (>300%) during charge and discharge hinder its large-scale application. The silicon-based negative electrode used in the prior art will inevitably have problems such as material pulverization and active material falling off from the current collector after multiple charge and discharge cycles, making its cycle life unable to meet the requirements of commercial applications. In order to further improve the structural stability of silicon-based negative electrodes, people have tried a variety of optimization measures, such as combining silicon materials with other metals for alloying, and using the good mechanical strength and conductivity of metals to improve the performance of silicon alloys. In addition, highly conductive carbon is used as a skeleton, and silicon is deposited on the carbon skeleton to obtain a silicon-carbon composite material with excellent cycle stability. However, the above methods all sacrifice part of the specific capacity to reduce the expansion effect; or use a very low-load silicon / carbon composite to obtain better stability in long-term cycles, but the overall silicon content decreases and the capacity advantage is weakened. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing a composite silicon-based negative electrode plate for a solid-state lithium-ion battery, aiming to solve the problem of insufficient silicon content in the negative electrode material, resulting in decreased capacity.

[0004] To solve the above technical problems, the present invention is implemented as follows: the present invention provides a method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery, the steps comprising: S1, screening micron-sized silicon particles and nano-sized silicon particles, and mixing them according to a weight ratio of the micron-sized silicon particles: the nano-sized silicon particles = 40-95: 5-60 to obtain a composite silicon component; S2, mixing the composite silicon component, conductive carbon black, functional filler and binder in a polar solvent to obtain a negative electrode slurry; S3. Coat the negative electrode slurry on the negative electrode current collector, and obtain a composite silicon-based negative electrode sheet after vacuum curing.

[0005] In some embodiments of the present invention, in step S2, the functional filler includes a carbon fiber tube, a conductive polymer, and an ion conductor; The binder comprises an outer layer binder, a middle layer binder and an inner layer binder, the outer layer binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride-hexafluoropropylene copolymer, the middle layer binder comprises at least one of styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid, and the inner layer binder comprises at least one of polyethylene oxide derivatives, polyacrylonitrile modified polymers, and polyvinylidene fluoride-hexafluoropropylene copolymer / lithium salt blends; The composite silicon component comprises an outer composite silicon component, a middle composite silicon component and an inner composite silicon component, wherein the weight ratio of the micron-sized silicon particles to the nano-sized silicon particles in the outer composite silicon component is 10-15:5-10, the weight ratio of the micron-sized silicon particles to the nano-sized silicon particles in the middle composite silicon component is 20-30:10-15, and the weight ratio of the micron-sized silicon particles to the nano-sized silicon particles in the inner composite silicon component is 40-50:5-8; The negative electrode slurry includes an inner layer coating, a middle layer coating and an outer layer coating sequentially coated on the surface of the negative electrode collector, the outer layer coating includes the outer layer composite silicon component, conductive carbon black, the outer layer binder and a polar solvent, the middle layer coating includes the middle layer composite silicon component, the carbon fiber tube, the middle layer binder, the conductive polymer and a polar solvent, and the inner layer coating includes the inner layer composite silicon component, the carbon fiber tube, the inner layer binder, the ion conductor and a polar solvent.

[0006] In some embodiments of the present invention, the conductive polymer includes a conductive monomer, and the conductive monomer includes at least one of pyrrole, aniline, and thiophene; The ion conductor comprises at least one of lithium phosphate, aluminum-doped lithium titanate phosphate, and cubic lithium lanthanum zirconium oxide; The polar solvent includes at least one of N-methylpyrrolidone, xylene and chlorobenzene.

[0007] In some embodiments of the present invention, based on weight percentage, in the outer coating, the outer layer composite silicon component accounts for 15-20wt%, the conductive carbon black accounts for 3-5wt%, the outer layer binder accounts for 5-10wt%, and the balance is the polar solvent; In the middle layer coating, the middle layer composite silicon component accounts for 30-45wt%, the carbon fiber tube accounts for 3-6wt%, the middle layer binder accounts for 5-10wt%, the conductive polymer accounts for 8-12wt%, and the balance is the polar solvent; In the inner layer coating, the inner layer composite silicon component accounts for 45-58wt%, the carbon fiber tube accounts for 2-5wt%, the inner layer binder accounts for 3-6wt%, the ion conductor accounts for 3-8wt%, and the balance is the polar solvent.

[0008] In some embodiments of the present invention, step S3 includes: S3.1, first coating the inner layer coating on the negative electrode current collector, and performing a semi-curing directional operation to form a first layer of directional arrangement of the carbon fiber tubes, wherein the thickness of the first layer is 15-25 μm; S3.2, coating the middle layer coating on the surface of the first layer, performing a semi-curing directional operation, and forming a second layer of the carbon fiber tubes arranged in a directional manner, wherein the thickness of the second layer is 5-10 μm; S3.3. Coating the outer layer coating on the surface of the second layer, performing vacuum curing operation to form a third layer, and obtaining a composite silicon-based negative electrode plate, wherein the thickness of the third layer is 5-10 μm.

[0009] In some embodiments of the present invention, the semi-curing orientation operation includes: First, raise the ambient temperature to 50-70°C, then introduce inert gas to form a semi-cured coating; Firstly, a horizontal shear force is applied to the semi-cured coating, and then a vertical magnetic field is applied to obtain a coating with directional arrangement of carbon fiber tubes; The coating with the carbon fiber tube directional arrangement is heated to 70-100° C., and a light source field is applied, and heated for 60-120 minutes to complete the semi-curing directional operation, wherein there are at least two light source points with different light intensities in the light source field.

[0010] In some embodiments of the present invention, step S1 comprises: S1.1. Put the selected micron-sized silicon particles and nano-sized silicon particles into a stirring container at a mass ratio of 40-95:5-60, add a low-polarity solvent, and stir at 50-100 rpm for 60-120 min to obtain a premix, wherein the low-polarity solvent includes at least one of n-hexane, cyclohexane, and toluene, the particle size of the micron-sized silicon particles is 1-5 μm, and the particle size of the nano-sized silicon particles is 30-200 nm; S1.2, adding a cross-linking agent to the premix and performing ball milling mixing, wherein the cross-linking agent comprises at least one of hexamethylene diisocyanate, N,N'-methylenebisacrylamide, and triethylenetetramine, the ball milling mixing time is 60 to 360 min, the ball mill speed is 50 to 400 r / min, and the ball-to-material ratio is 1:1 to 10:1; S1.3, filtering or centrifuging the premix after ball milling, heating to 80-100° C. in a vacuum environment and drying for 240-360 min to obtain a composite silicon component.

[0011] Compared with the prior art, the method for preparing the composite silicon-based negative electrode sheet for solid-state lithium-ion batteries in the present invention has the following beneficial effects: Nano-scale silicon particles have a large specific surface area and many active sites, which can provide a higher specific capacity; micron-scale silicon particles play a skeletal support role in the overall structure, effectively utilizing the high theoretical specific capacity of silicon, thereby increasing the energy density of the battery. Pure nano-silicon or pure micron-silicon often causes electrode pulverization and shedding due to volume expansion. Through the synergy of reasonably proportioned micron-silicon and nano-silicon, the volume change can be better buffered during the charge and discharge process, reducing structural damage and improving the cycle stability of the battery. Conductive carbon black and functional fillers form an effective electron transmission network in the pole piece, which is evenly distributed with the composite silicon components, which can significantly reduce the internal resistance of the electrode, enhance the efficiency of ion and electron transmission, and improve the rate performance.

[0012] The use of micron-scale and nano-scale particles allows the negative electrode slurry to take into account viscosity, dispersibility and film quality during the electrode coating and vacuum curing process, and obtain a uniform and dense negative electrode. Curing the electrode in a vacuum environment can more effectively discharge solvents and bubbles, reduce the generation of defects such as holes and cracks, and further enhance the mechanical strength and electrochemical stability of the negative electrode.

[0013] In summary, the negative electrode sheet made of a composite of micron-scale silicon and nano-scale silicon in combination with a conductive agent, functional filler and binder can not only give full play to the high capacity advantage of silicon materials, but also overcome the problem of electrode failure caused by silicon volume expansion to a certain extent, bringing higher specific capacity, longer cycle life and better rate performance to lithium-ion batteries, and improving the overall energy density and reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic flow chart of a method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery in one embodiment of the present invention; Figure 2 is a scanning electron microscope (SEM) image of the composite silicon-based negative electrode sheet prepared in Example 1 of the present invention; Figure 3is a scanning electron microscope (SEM) image of the composite silicon-based negative electrode sheet prepared in Example 2 of the present invention; Figure 4 is a scanning electron microscope (SEM) image of the composite silicon-based negative electrode sheet prepared in Example 3 of the present invention; Figure 5 is a scanning electron microscope (SEM) image of the composite silicon-based negative electrode plate prepared in Example 2 of the present invention during the delithiation process; Figure 6 is a scanning electron microscope (SEM) image of the composite silicon-based negative electrode sheet prepared in Comparative Example 1 of the present invention; Figure 7 is a scanning electron microscope (SEM) image of the composite silicon-based negative electrode sheet prepared in Comparative Example 2 of the present invention; Figure 8 It is a schematic diagram of the working mechanism of the composite silicon-based negative electrode plate prepared in one embodiment of the present invention. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0016] Please refer to Figure 1 and Figure 8 The present invention provides a method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery, the steps comprising: S1. Screening micron-sized silicon particles and nano-sized silicon particles, and mixing them according to a weight ratio of micron-sized silicon particles: nano-sized silicon particles = 40-95: 5-60 to obtain a composite silicon component.

[0017] Nano-sized silicon particles, due to their high specific surface area, can provide more active sites and significantly increase the theoretical specific capacity of the electrode. Micro-sized silicon particles are more mechanically stable than nano-sized silicon particles during volume expansion, reducing electrode pulverization and cracking caused by expansion and extending the cycle life of the battery.

[0018] Nano-sized silicon particles are easy to agglomerate. By mixing with micron-sized silicon particles, nano-silicon can be effectively dispersed, reducing agglomeration and ensuring uniform distribution inside the electrode. Nano-silicon can fill the pores between micron-sized silicon particles, improve the overall density, reduce the porosity inside the electrode, and improve the overall stability of the electrode.

[0019] During the charge and discharge process, silicon particles undergo significant volume changes. Micron-sized silicon provides high capacity as the main carrier, while nano-sized silicon acts as a buffer material during the expansion of micron-sized silicon, slowing down the impact of the overall volume change on the electrode structure and preventing the peeling and breakage of the electrode material. The introduction of nano-sized silicon particles helps to form a tighter conductive network, enhance the electron conduction path, and improve the conductivity of the electrode. The high surface area of ​​nano-silicon makes it more active in electrochemical reactions, improving the initial capacity and rate performance of the electrode.

[0020] At the same time, the introduction of nano-sized silicon particles promotes the uniform distribution of conductive carbon black or other conductive additives, forming a more complete conductive network, improving the electron transfer efficiency of the electrode, and reducing the internal resistance of the electrode. The optimized conductive network not only improves the overall conductivity of the electrode, but also enhances the performance of the electrode during high-rate discharge, ensuring the stability and efficiency of the battery under fast charge and discharge conditions.

[0021] Step S1 includes: S1.1. Put the screened micron-sized silicon particles and nano-sized silicon particles into a stirring container at a mass ratio of 40-95:5-60, add a low-polarity solvent, and stir at 50-100 rpm, for example, 50 rpm, 80 rpm, 100 rpm, for 60-120 min, for example, 60 min, 80 min, 120 min, to obtain a premix, wherein the low-polarity solvent includes at least one of n-hexane, cyclohexane, and toluene, the particle size of the micron-sized silicon particles is 1-5 μm, for example, 1 μm, 3 μm, and 5 μm, and the particle size of the nano-sized silicon particles is 30-200 nm, for example, 30 nm, 100 nm, and 200 nm.

[0022] Low-polarity solvents can reduce the strong mutual attraction between nano-sized silicon particles, making nano-sized silicon easier to wet and disperse around micro-sized silicon under relatively low shear stirring, effectively avoiding large-scale agglomeration of nano-sized silicon particles and laying a foundation for uniform dispersion for subsequent ball milling and cross-linking.

[0023] During the stirring process, nano-silicon will be partially adsorbed / embedded in the surface pits or pores of micron silicon particles, forming a preliminary fit or micro-nano interlocking structure. This reduces the direct shedding or random agglomeration of nano-silicon during subsequent intense mixing, and improves the stability of the micro-nano particle interface. Low-polarity solvents have a certain effect of cleaning and removing a small amount of surface impurities. At the same time, the mild conditions during the stirring process avoid further oxidation of the silicon surface at high temperatures. While ensuring the purity of the silicon particles, the original surface morphology of the particles will not be destroyed, laying a good foundation for a tighter micro-nano composite.

[0024] S1.2. Add a cross-linking agent to the premix and perform ball milling mixing, wherein the cross-linking agent includes at least one of hexamethylene diisocyanate, N,N'-methylenebisacrylamide, and triethylenetetramine. The ball milling mixing time is 60 to 360 min, for example, 60 min, 200 min, and 360 min. The speed of the ball mill is 50 to 400 r / min, for example, 50 r / min, 100 r / min, and 400 r / min. The ball-to-material ratio is 1:1 to 10:1, for example, 1:1, 5:1, and 10:1.

[0025] Under the mechanical force of ball milling, the cross-linking agent can chemically bond / bridge with the active groups on the surface of silicon particles or between them, making the nano-silicon more firmly anchored on the surface of micro-silicon, forming a micro-nano composite structure with chemical bond connection, and reducing the separation or shedding caused by the weak van der Waals force between particles.

[0026] The medium / high energy impact and shear force brought by ball milling can further break up the remaining agglomerates and make the nano-silicon more evenly coated on the surface of micro-silicon. At the same time, the cross-linking agent is more easily penetrated into the interface under the participation of mechanical force. The dispersion and interfacial bonding strength between micro-nano particles are significantly improved, making the composite silicon component more stable in the subsequent pulping or coating process.

[0027] By adjusting the ball milling time, rotation speed and ball-to-material ratio, the degree of silicon particle crushing, particle size distribution and dispersion depth of the crosslinking agent can be controlled. The process has strong applicability, which can avoid excessive damage to silicon particles and obtain sufficiently high dispersion and interface crosslinking efficiency, providing adjustable space for different application requirements.

[0028] S1.3. Filter or centrifuge the premix after ball milling, heat to 80-100°C in a vacuum environment and dry for 240-360 min, for example, 80°C, 90°C, 100°C, 240 min, 300 min, 360 min, to obtain a composite silicon component.

[0029] By filtering or centrifuging, the excess solvent and unreacted crosslinking agent solution are first separated, and then dried for a long time under vacuum conditions to completely evaporate the residual solvent or low molecular weight by-products. Dry and pure composite silicon powder is obtained, which reduces the negative impact on the subsequent slurry viscosity and binder system.

[0030] Vacuum drying not only removes the solvent, but also helps the cross-linking agent to further react and solidify at the interface. The micro-nano silicon particles form a chemically locked or semi-solidified structure. This ensures that the composite silicon powder can maintain the constructed micro-nano bonding during storage, transportation and subsequent electrode preparation without large-scale agglomeration or stratification.

[0031] Through drying, the solid content, particle morphology and surface characteristics of the composite silicon components can be accurately controlled, so that the proportions are more accurate and the dispersion is more reliable when preparing the negative electrode slurry. When preparing the electrode, there is no need for secondary large-scale drying or impurity removal, which improves production efficiency and reduces the loss of micro-nano silicon.

[0032] S2. Mixing the composite silicon component, conductive carbon black, functional filler and binder in a polar solvent to obtain a negative electrode slurry.

[0033] The binder comprises an outer layer binder, a middle layer binder and an inner layer binder, the outer layer binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyvinylidene fluoride-hexafluoropropylene copolymer, the middle layer binder comprises at least one of styrene-butadiene rubber, carboxymethyl cellulose and polyacrylic acid, and the inner layer binder comprises at least one of polyethylene oxide derivatives, polyacrylonitrile modified polymers and polyvinylidene fluoride-hexafluoropropylene copolymer / lithium salt blends; The composite silicon component includes an outer composite silicon component, a middle composite silicon component and an inner composite silicon component, wherein the weight ratio of micron-sized silicon particles to nano-sized silicon particles in the outer composite silicon component is 10-15:5-10, the weight ratio of micron-sized silicon particles to nano-sized silicon particles in the middle composite silicon component is 20-30:10-15, and the weight ratio of micron-sized silicon particles to nano-sized silicon particles in the inner composite silicon component is 40-50:5-8; The negative electrode slurry includes an inner layer coating, a middle layer coating and an outer layer coating which are sequentially coated on the surface of the negative electrode collector. The outer layer coating includes an outer layer composite silicon component, conductive carbon black, an outer layer binder and a polar solvent. The middle layer coating includes a middle layer composite silicon component, a carbon fiber tube, a middle layer binder, a conductive polymer and a polar solvent. The inner layer coating includes an inner layer composite silicon component, a carbon fiber tube, an inner layer binder, an ion conductor and a polar solvent.

[0034] Through the distribution of micro-nano silicon at different levels, the inner layer provides high capacity, the middle layer is moderate, and the outer layer guarantees basic capacity and conductivity. The elastic middle layer binder and carbon fiber tube effectively buffer the volume change of silicon, reduce electrode pulverization and structural damage, and extend the cycle life of the battery.

[0035] The conductive carbon black on the outer layer, the conductive polymer on the middle layer and the ionic conductor on the inner layer together build an efficient electron and ion transport network, improving the overall performance of the battery. The different layers of conductive materials ensure that the electrode has good conductivity in all directions, reducing internal resistance and improving rate performance.

[0036] The orderly arrangement of carbon fiber tubes enhances the mechanical strength and structural stability of the electrode, preventing crack propagation and electrode deformation under high stress. Different types of binders play specific functions in each layer, ensuring a strong bond between layers and between the electrode and the current collector, and improving the overall toughness and durability of the electrode. The inner layer ion conductor improves the ion conductivity of the electrode and optimizes the battery's charge and discharge efficiency and performance stability.

[0037] Through layered coating and directional operation, the functional materials of each layer are evenly distributed, avoiding excessive agglomeration and inhomogeneity of the materials. The binders and functional fillers at different levels are compatible with each other in the slurry, ensuring the overall stability and consistency of the multi-layer structure.

[0038] The high proportion of micron silicon in the inner layer combined with an appropriate amount of nano silicon provides excellent specific capacity to meet the needs of high energy density batteries. The elastic binder and carbon fiber tube in the middle layer effectively buffer the volume change of silicon, reduce electrode pulverization and structural damage, and extend the cycle life of the battery. The reasonable layout of multi-layer conductive materials and ion conductors builds an efficient electron and ion transmission network, improving the overall performance and rate capability of the battery. The directional arrangement of carbon fiber tubes and the multi-layer binder system enhance the mechanical strength and structural stability of the electrode and prevent crack propagation under high stress conditions. The conductive polymer and functional filler in the middle layer give the electrode self-healing ability, ensuring that the electrode can automatically restore the conductive path after damage, thereby improving the reliability and life of the battery. The layered coating and directional operation ensure the uniform distribution and functionality of the material in each layer, avoid excessive agglomeration and inhomogeneity of the material, and improve the overall performance of the electrode.

[0039] For the composite silicon components in different layers, the specific mixing ratios of micrometer-sized silicon particles and nanometer-sized silicon particles are set to be different during the preparation of the composite silicon component of S1, and are added when the specific coating is prepared.

[0040] The conductive polymer includes a conductive monomer, the conductive monomer includes at least one of pyrrole, aniline, and thiophene, the ion conductor includes at least one of lithium phosphate, aluminum-doped lithium titanate phosphate, and cubic lithium lanthanum zirconium oxide, and the polar solvent includes at least one of N-methylpyrrolidone, xylene, and chlorobenzene.

[0041] According to the weight percentage, in the outer coating, the outer layer composite silicon component accounts for 15~20wt%, the conductive carbon black accounts for 3~5wt%, the outer layer binder accounts for 5~10wt%, and the balance is a polar solvent. Most of the outer layer binder is a fluorine-based binder with excellent chemical stability and mechanical strength, forming a solid protective layer to prevent the external environment (such as electrolyte or solid electrolyte) from corroding and oxidizing the electrode material, which can improve the chemical stability of the outer coating, reduce the occurrence of side reactions, and improve the stability and life of the electrode during the cycle.

[0042] Conductive carbon black forms a preliminary electron transmission path in the outer layer, which improves the overall conductivity of the electrode, ensures that electrons can be efficiently transmitted to the current collector, and reduces the internal resistance of the electrode.

[0043] The appropriate amount of nano-silicon in the outer composite silicon component fills the pores between the micron silicon particles, improves the overall density, and provides a moderate specific capacity. Nano-silicon filling helps reduce the agglomeration of micron silicon, ensures the uniform distribution of the outer specific capacity, improves the chemical stability of the outer coating, reduces the occurrence of side reactions, and improves the stability and life of the electrode during the cycle.

[0044] In the middle layer coating, the middle layer composite silicon component accounts for 30~45wt%, the carbon fiber tube accounts for 3~6wt%, the middle layer binder accounts for 5~10wt%, the conductive polymer accounts for 8~12wt%, and the balance is polar solvent. The higher proportion of micron silicon in the middle layer composite silicon component provides the main specific capacity to meet the high energy density requirements. Nano silicon acts as a buffer material during the volume change of micron silicon, reducing the impact of silicon expansion on the electrode structure.

[0045] The middle layer binder is an elastic binder that gives the middle layer electrode good flexibility and elasticity, which can effectively buffer the volume change of silicon particles during the charging and discharging process and reduce electrode pulverization and crack propagation.

[0046] The conductive polymer forms an efficient electron transmission path in the middle layer, improving the overall conductivity of the electrode. At the same time, the conductive polymer works synergistically with the carbon fiber tube to form a stable and efficient conductive network, ensuring efficient transmission of electrons inside the electrode.

[0047] The specific structure of the conductive polymer may include a conductive monomer and a reversible chemical bond arranged outside the conductive monomer, wherein the reversible chemical bond includes at least one of a disulfide bond, an amide bond, and an ester bond. Connected to the main chain or side chain of the conductive monomer. When the material is subjected to external force or cracks, the broken chemical bonds can be reformed under external stimulation to restore the polymer network.

[0048] At moderate temperatures (such as 60~120℃), disulfide bonds will undergo a reversible exchange reaction, breaking / rearranging into new disulfide bonds, reconnecting the molecular chains at the breaks. Some disulfide bonds will undergo photochemically induced disulfide bond breakage and recombination under light (especially ultraviolet light, wavelength of about 300~365nm).

[0049] Amide bonds and ester bonds are more susceptible to reversible hydrolysis and re-esterification / re-amidation at specific pH levels; or the addition of metal ions can trigger dynamic rearrangement of coordination bonds. In a strongly acidic environment with a pH of less than 2, ester bonds are susceptible to acid-catalyzed hydrolysis to generate carboxylic acids and alcohols. Subsequently, if water is removed or a suitable dehydrating agent is used, combined with a suitable temperature, esterification / re-esterification occurs, allowing the broken ester bonds to recombine. In a strongly alkaline environment with a pH of more than 10, ester bonds are more susceptible to saponification to generate carboxylates and alcohols; when the environment returns to the conditions required for a reversible reaction (such as neutrality or the addition of an esterification catalyst, an alcohol source is added, and the temperature is increased), some ester bonds are reformed (re-esterification).

[0050] The specific structure of the conductive polymer may include a conductive monomer and a curing composition, the curing composition includes an external enclosure wall and a repair object, the enclosure wall encloses a placement cavity, the repair object is arranged in the placement cavity, and the repair object includes at least one of an epoxy precursor and a curing agent, dicyclopentadiene and a catalyst, an isocyanate and a polyol. Among them, the enclosure wall includes at least one of urea-formaldehyde resin and polyurea formaldehyde, the curing composition will be subjected to external stimulation (such as heating, or being squeezed by external force), and the enclosure wall will rupture. When the curing composition ruptures, the isocyanate reacts with the polyol to form a polyurethane (PU) to generate an elastomer, which acts as a crack filling material and provides a certain toughness.

[0051] When the epoxy precursor is bisphenol A type or glycidyl ether type epoxy resin and is combined with a curing agent (such as amines), it can be quickly cured at the cracks and mixed to form a network epoxy resin to fill the cracks and restore the structural strength.

[0052] Dicyclopentadiene and the catalyst trigger ring-opening metathesis polymerization to form poly(dicyclopentadiene) near the crack, repair the fracture surface, cure quickly, and have a tight polymer network, which can enhance both mechanical properties and structural integrity. The catalyst can be a Grubbs catalyst.

[0053] The carbon fiber tube forms an orderly mechanical support network in the middle layer, which improves the mechanical strength and structural stability of the electrode and prevents electrode deformation and crack propagation under high stress conditions.

[0054] The solidified composition is randomly or orderly distributed inside the electrode coating. When the crack expands in the electrode, it is very likely to pass through or approach certain areas where the solidified composition is located. When the crack advances forward, this difference causes the enclosure wall to be easily broken by force. There is often a stress concentration phenomenon at the crack tip (crack front). When the crack tip approaches the surrounding area of ​​the enclosure wall, the local stress rises rapidly, and the enclosure wall is more likely to break under stress impact.

[0055] Under the synergistic effect of the conductive polymer and the carbon fiber tube, when cracks occur in the electrode, the conductive polymer can form a conductive path at the crack, and the carbon fiber tube further enhances the mechanical strength of the crack, realizing the self-repair function of the electrode and extending the battery life.

[0056] In the inner coating, the inner composite silicon component accounts for 45-58wt%, the carbon fiber tube accounts for 2-5wt%, the inner binder accounts for 3-6wt%, the ion conductor accounts for 3-8wt%, and the balance is a polar solvent.

[0057] The inner layer of composite silicon contains the highest proportion of micron silicon, providing the largest specific capacity and meeting the high energy density requirements of the battery. At the same time, a small amount of nano silicon helps fill the pores between micron silicon and improve the density and stability of the inner layer.

[0058] Ion conductors improve the transmission efficiency of lithium ions, reduce interfacial impedance, and optimize the charge and discharge performance of the battery. High ionic conductivity ensures that the battery can maintain excellent performance at high rates.

[0059] The inner layer binder enhances the bonding force between the inner layer and the current collector, ensures the firm bonding between the electrode and the current collector, prevents interface detachment, and improves the overall structural integrity and stability of the electrode. It optimizes the ion conduction and electron transmission of the inner layer, ensures the stability of the interface reaction during the battery charge and discharge process, reduces the occurrence of side reactions, and improves the cycle stability and life of the electrode.

[0060] Through the fine design and proportion of the three layers of coating, the outer layer, the middle layer and the inner layer, various technical optimizations have been achieved, including: the appropriate amount of composite silicon components in the outer layer provide the basic specific capacity, and nano-silicon fills the pores to improve the uniform distribution of the specific capacity. The high proportion of micron silicon in the middle layer provides the main specific capacity, and the elastic binder and carbon fiber tube buffer the volume change of silicon, reduce pulverization and crack propagation, and extend the cycle life. The highest proportion of micron silicon in the inner layer provides the maximum specific capacity, and the ion conductor improves the ion conduction efficiency, ensuring the high energy density and excellent performance of the battery. The conductive carbon black in the outer layer, the conductive polymer in the middle layer, and the ion conductor in the inner layer jointly construct an efficient electron and ion transmission network, improving the overall conductivity and rate performance of the battery. The fluorine-based binder in the outer layer provides solid surface protection, the elastic binder in the middle layer provides flexibility, and the ion conductive modified binder in the inner layer ensures the firm bonding between the inner layer and the current collector, which improves the mechanical strength and structural stability of the electrode as a whole.

[0061] S3. Coat the negative electrode slurry on the negative electrode current collector, and obtain a composite silicon-based negative electrode sheet after vacuum curing.

[0062] Step S3 includes: S3.1. First apply the inner coating on the negative electrode current collector and perform a semi-curing directional operation to form the first layer of directional arrangement of carbon fiber tubes, wherein the thickness of the first layer is 15-25 μm. The inner coating often contains the highest proportion of micron-sized silicon, providing the main specific capacity. Through the semi-curing directional operation, an external field or specific mechanical treatment is applied before the film is fully cured to allow the carbon fiber tubes to be oriented in the slurry.

[0063] The large proportion of silicon in the inner layer provides the overall energy density, and the directional distribution of the carbon fiber tubes forms a stable and orderly electron channel between the inner layer and the current collector, reducing the internal resistance of the pole piece; in the semi-curing stage, the binder is fully bonded to the surface of the current collector to reduce interface delamination. Since the volume of silicon changes significantly during charging and discharging, the directional support of the carbon fiber tubes in the inner layer can absorb impact, hinder the spread of microcracks, strengthen the mechanical stability of the inner layer, and extend the cycle life of the pole piece.

[0064] Among them, the semi-curing directional operation includes: First, raise the ambient temperature to 50~70℃, then introduce inert gas to form a semi-cured coating.

[0065] Partially volatilize or discharge the polar solvent, so that the coating transitions from a more fluid slurry state to a "semi-cured" stage (viscoelastic / gel state). An inert gas environment (such as nitrogen, argon) can reduce the effects of oxidation or humidity and maintain the chemical stability of the electrode material. At this temperature and inert atmosphere, the viscosity of the coating increases moderately but is not fully cured, and the carbon fiber tube and other functional fillers can still rotate or move freely in the external force field.

[0066] First, a horizontal shear force is applied to the semi-cured coating, and then a vertical magnetic field is applied to obtain a coating with directional arrangement of carbon fiber tubes.

[0067] The carbon fiber tubes are initially induced to be arranged along the coating surface in the direction of the shear force, reducing random agglomeration. Applying a vertical magnetic field on the surface of the carbon fiber tube can orient the carbon fiber tube and enhance the mechanical and electrical properties. By applying two external fields, first horizontal and then vertical, a more complex multi-directional weaving or layered arrangement appears inside the coating, improving the mechanical toughness and anisotropic conductivity. The viscosity of the semi-cured state is moderate, which will not cause excessive sedimentation or aggregation of the carbon fiber tube, and the orientation effect is more stable.

[0068] The carbon fiber tube itself has a certain graphite layered structure, and it will show anisotropy of electron distribution at the microscopic level (that is, there are different magnetic susceptibilities in the "axial" and "radial" directions). When the carbon fiber tube is placed in an external magnetic field, if the axial and radial directions of the carbon fiber tube respond differently to the magnetic field, the carbon fiber tube will tend to align along the direction with smaller magnetic susceptibility or more stable energy. Although the carbon fiber tube is weakly paramagnetic or weakly diamagnetic as a whole, the local orientation is not uniform, and there is still a considerable orientation effect in a strong magnetic field.

[0069] The coating with the carbon fiber tubes arranged in a directional manner is heated to 70-100°C, and a light source field is applied, and heated for 60-120 minutes to complete the semi-curing directional operation, wherein there are at least two light source points with different light intensities in the light source field.

[0070] While heating to 70-100°C, at least two levels of light intensities are applied. There will be a difference in curing rate between the coating surface and the interior, which can achieve layered or gradient curing. The surface layer will cure first or cure more thoroughly to provide certain protection and mechanical support. The middle and lower layers will gradually complete cross-linking and reduce internal stress accumulation under relatively weak light intensity (or milder curing conditions).

[0071] If only a single strong light is used, the surface curing speed is too fast, which may cause the internal solvent and gas to be discharged in time, causing bubbles or stress concentration. Through light intensity difference and graded curing, these defects can be significantly reduced, reducing curing defects such as holes, cracks, bubbles, etc., and improving the mechanical integrity and density of the final electrode.

[0072] Since the coating maintains a certain viscosity and is partially cross-linked at 70-100°C, the carbon fiber tube structure that has been oriented by external force or magnetic force can be locked after the coating viscosity increases, and maintain the expected orderly arrangement when the final curing is completed, avoiding "spontaneous rebound" or disorder in the later high temperature or final curing stage, and ensuring the design effect of multi-directional reinforcement or conductive network.

[0073] The weaker light intensity area can make the local coating maintain a little fluidity, allowing the fiber tube to complete fine-tuning alignment; the stronger light intensity area quickly solidifies the surface or specific parts to form an early support, taking into account the uniform dispersion and rapid local fixation of the coating, reducing the uneven thickness caused by coating collapse or flow.

[0074] If "strong light zone" and "weak light zone" are set in the light source field, or even differentiated irradiation is performed on different positions, local differential curing can be formed in the same layer of coating. The strong light zone has a higher hardness or is cured more thoroughly, while the weak light zone has better toughness or has room for subsequent reaction, thereby meeting the mechanical or conductive requirements of different parts and improving the overall functional diversity of the electrode.

[0075] Two or more light intensities combined with temperature curing allow the outer layer and the deep layer to achieve the most suitable curing speed and degree respectively. The oriented carbon fiber tube in the semi-cured viscoelastic state is "frozen" by subsequent heating + light irradiation to reduce the disorder of the arrangement. Staged curing avoids interface peeling, holes or internal cracks caused by "over-fast curing", and the density and mechanical strength of the pole piece are improved. By adjusting the light source layout, light intensity and temperature gradient, the curing efficiency and the final performance of the coating can be flexibly controlled to meet the requirements of different formulations or thicknesses.

[0076] S3.2, coating a middle layer of coating on the surface of the first layer, and performing a semi-curing directional operation to form a second layer of directional arrangement of carbon fiber tubes, wherein the thickness of the second layer is 5-10 μm.

[0077] The middle layer coating is usually located between the inner layer with high silicon loading and the outer layer for surface protection, playing a connecting role. When the middle layer is not fully cured, it forms a good interface with the inner layer, reducing the risk of delamination or delamination. The middle layer is thin and uniform, allowing the outer layer to be well coated and stably bonded on it. It enhances the interlayer adhesion between the inner and outer layers, prevents the interface separation of the multilayer structure under cycling or stress, and improves the overall mechanical strength and long-term stability of the electrode.

[0078] The carbon fiber tubes in the first and second layers can be arranged in the same direction, and the cumulative effect of optimizing the conductivity / mechanical properties in a single direction is significant, further improving the electron transmission rate and structural strength in this direction. The carbon fiber tubes in the first and second layers can have an angle (such as 90°, 45°, etc.), which improves the overall anisotropy regulation of the material, and can enhance the conductivity and mechanical support in multiple directions. If the angle is 90°, it can form a "woven structure" that not only enhances the shear strength, but also allows the electrode to disperse the current more evenly in a two-dimensional plane.

[0079] S3.3. Apply an outer coating on the surface of the second layer and perform vacuum curing to form a third layer to obtain a composite silicon-based negative electrode sheet, wherein the thickness of the third layer is 5 to 10 μm.

[0080] Curing in a vacuum environment can more effectively expel residual solvents and bubbles inside or between layers of the coating, avoid air or moisture inclusions, reduce holes and micro-defects, enhance the density and uniformity of the coating, and improve the overall mechanical strength and durability of the pole piece.

[0081] The outer layer is only 5~10 μm thick, which is relatively thin but sufficient to form a chemical and mechanical protective barrier to block the corrosion or side reactions that may occur to the electrode active materials (especially the silicon negative electrode) from the external environment, reduce the direct contact between the electrolyte or external oxidizing substances and the negative electrode active layer, extend the battery cycle life, improve the chemical stability of the electrode, and reduce the capacity decay rate. Maintain or enhance the ion and electron transmission efficiency of the electrode, promote rapid kinetic response, and balance the needs of "encapsulation protection" and "high conduction".

[0082] The negative electrode current collector material needs to have good conductivity, corrosion resistance and electrochemical compatibility with the negative electrode material. The negative electrode current collector can be at least one of copper foil, nickel foil, nickel-based metal nickel, and stainless steel foil. It has excellent corrosion resistance and high conductivity and can be used in specific high temperatures or special electrolyte systems.

[0083] Please refer to Figure 2In Example 1, the particle size of the micron-sized silicon particles is about 1 μm, and the particle size of the nano-sized silicon particles is about 200 nm; Please refer to Figure 3 and Figure 5 In Example 2, the particle size of the micron-sized silicon particles is about 3 μm, and the particle size of the nano-sized silicon particles is about 200 nm; Please refer to Figure 4 In Example 3, the particle size of the micron-sized silicon particles is about 2 μm, and the particle size of the nano-sized silicon particles is about 200 nm; In Example 4, the particle size of the micron-sized silicon particles is about 2 μm, and the particle size of the nano-sized silicon particles is about 100 nm; In Example 5, the particle size of the micron-sized silicon particles is about 1 μm, and the particle size of the nano-sized silicon particles is about 100 nm.

[0084] Please refer to Figure 6 The difference between Comparative Example 1 and Example 1 is that the composite silicon component only includes micron-sized silicon particles with a particle size of about 1 micron, and does not contain nano-sized silicon particles.

[0085] Please refer to Figure 7 The difference between Comparative Example 2 and Example 1 is that the composite silicon component only includes nano-sized silicon particles with a particle size of about 100 nanometers, and does not contain micron-sized silicon particles.

[0086] The difference between Comparative Example 3 and Example 1 is that the negative electrode slurry only includes the composite silicon negative electrode material and the binder, and does not contain conductive carbon black.

[0087] experiment: 1. Test object: The silicon-based negative electrode all-solid-state lithium-ion batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were used as test objects in this test example.

[0088] The silicon-based composite silicon-based negative electrode sheets prepared in Examples 1 to 5 and Comparative Examples 1 to 3 are cut into pieces and placed on one side of the solid-state battery. The sulfide solid electrolyte powder is poured in and pressed into sheets at a pressure of 375MPa. A lithium-indium alloy is used as the counter electrode to prepare a silicon-based negative electrode all-solid-state lithium-ion battery. The charge and discharge cut-off voltage is -0.595V~0.9V. The specific test items are: (1) Rate performance test at room temperature, first 0.1C constant current charge and discharge, then 0.5C and 1C constant current charge and discharge in sequence; (2) Cycle performance test, first 0.1C constant current charge and discharge, then 0.3C constant current charge and discharge; The experimental results are shown in Table 1. Table 1: Experimental results: Examples 1 to 5 are all "micron-sized silicon + nano-sized silicon" composites. Compared with the control groups containing only micron-sized silicon or only nano-sized silicon, the capacity at 0.1C, 0.5C, and 1C discharge rates and after 50 cycles is higher and the attenuation is smaller. Comparative Example 1 (containing only micron-sized silicon, not containing nano-sized silicon) has a 1C capacity of only 376.9 mAh / g, which is significantly inferior to the embodiment containing nano-sized silicon. This shows that the use of only micron-sized silicon is prone to problems such as insufficient conductivity and difficulty in buffering volume expansion, and the rate performance and cycle stability are relatively poor. Comparative Example 2 (containing only nano-sized silicon, not containing micron-sized silicon) has a high capacity of 3161.3 mAh / g at 0.1C, but only 1440.1 mAh / g at a high rate of 1C, which is lower than most embodiments (such as Examples 3 and 4). This shows that although high capacity can be obtained by using only nano-sized silicon, it is still inferior to the comprehensive performance brought by the synergy of "micron + nano" at a certain rate. The composite of micron-sized silicon and nano-sized silicon can take into account both the mechanical stability of micron-sized silicon particles and the high specific surface area activity of nano-sized silicon, thereby maintaining higher capacity at high rates and having good stability during cycling.

[0089] Example 3 (micron silicon 2μm + nano silicon 200nm) and Example 4 (micron silicon 2μm + nano silicon 100nm) have high capacities at 0.1C, 0.5C, and 1C, and high capacities after cycling (2517.4 and 2689.2 mAh / g, respectively). Example 4 even achieved a 1C lithium removal capacity of 2412.5 mAh / g and a capacity of 2689.2 mAh / g after 50 cycles, which is one of the highest levels, showing the efficient synergy of particle size 2μm (micron silicon) + 100nm (nano silicon) in this system. For specific formulas, the combination of "micron silicon 2μm + nano silicon 100~200 nm" can achieve an excellent balance between the specific surface area and mechanical stability of the material, significantly improving both rate performance and cycle life.

[0090] In comparative example 3 (conductive carbon black removed, only "composite silicon + binder"), the 0.1C capacity is still relatively high (2639.1 mAh / g), but the 1C capacity drops sharply to 189.3 mAh / g, and only 787.5 mAh / g after 50 cycles. It can be seen that not adding conductive carbon black will lead to an imperfect overall conductive network, and the high-rate performance and cycle stability are severely limited. Conductive agents (such as carbon black) play an indispensable role in building a stable electron transmission path and improving high-rate discharge capability and cycle life.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery, characterized in that the steps include: S1, screening micron-sized silicon particles and nano-sized silicon particles, and mixing them according to a weight ratio of the micron-sized silicon particles: the nano-sized silicon particles = 40-95: 5-60 to obtain a composite silicon component; S2, mixing the composite silicon component, conductive carbon black, functional filler and binder in a polar solvent to obtain a negative electrode slurry; S3. Coat the negative electrode slurry on the negative electrode current collector, and obtain a composite silicon-based negative electrode sheet after vacuum curing.

2. The method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery according to claim 1, characterized in that: In the step S2, the functional filler includes carbon fiber tubes, conductive polymers and ion conductors; The binder comprises an outer layer binder, a middle layer binder and an inner layer binder, the outer layer binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride-hexafluoropropylene copolymer, the middle layer binder comprises at least one of styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid, and the inner layer binder comprises at least one of polyethylene oxide derivatives, polyacrylonitrile modified polymers, and polyvinylidene fluoride-hexafluoropropylene copolymer / lithium salt blends; The composite silicon component comprises an outer composite silicon component, a middle composite silicon component and an inner composite silicon component, wherein the weight ratio of the micron-sized silicon particles to the nano-sized silicon particles in the outer composite silicon component is 10-15:5-10, the weight ratio of the micron-sized silicon particles to the nano-sized silicon particles in the middle composite silicon component is 20-30:10-15, and the weight ratio of the micron-sized silicon particles to the nano-sized silicon particles in the inner composite silicon component is 40-50:5-8; The negative electrode slurry includes an inner layer coating, a middle layer coating and an outer layer coating sequentially coated on the surface of the negative electrode collector, the outer layer coating includes the outer layer composite silicon component, conductive carbon black, the outer layer binder and a polar solvent, the middle layer coating includes the middle layer composite silicon component, the carbon fiber tube, the middle layer binder, the conductive polymer and a polar solvent, and the inner layer coating includes the inner layer composite silicon component, the carbon fiber tube, the inner layer binder, the ion conductor and a polar solvent.

3. The method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery according to claim 2, characterized in that: The conductive polymer includes a conductive monomer, and the conductive monomer includes at least one of pyrrole, aniline, and thiophene; The ion conductor comprises at least one of lithium phosphate, aluminum-doped lithium titanate phosphate, and cubic lithium lanthanum zirconium oxide; The polar solvent includes at least one of N-methylpyrrolidone, xylene and chlorobenzene.

4. The method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery according to claim 2, characterized in that: According to weight percentage, in the outer coating, the outer composite silicon component accounts for 15-20wt%, the conductive carbon black accounts for 3-5wt%, the outer binder accounts for 5-10wt%, and the balance is the polar solvent; In the middle layer coating, the middle layer composite silicon component accounts for 30-45wt%, the carbon fiber tube accounts for 3-6wt%, the middle layer binder accounts for 5-10wt%, the conductive polymer accounts for 8-12wt%, and the balance is the polar solvent; In the inner layer coating, the inner layer composite silicon component accounts for 45-58wt%, the carbon fiber tube accounts for 2-5wt%, the inner layer binder accounts for 3-6wt%, the ion conductor accounts for 3-8wt%, and the balance is the polar solvent.

5. The method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery according to any one of claims 2 to 4, characterized in that: The step S3 comprises: S3.1, first coating the inner layer coating on the negative electrode current collector, and performing a semi-curing directional operation to form a first layer of directional arrangement of the carbon fiber tubes, wherein the thickness of the first layer is 15-25 μm; S3.2, coating the middle layer coating on the surface of the first layer, performing a semi-curing directional operation, and forming a second layer of the carbon fiber tubes arranged in a directional manner, wherein the thickness of the second layer is 5-10 μm; S3.

3. Coating the outer layer coating on the surface of the second layer, performing vacuum curing operation to form a third layer, and obtaining a composite silicon-based negative electrode plate, wherein the thickness of the third layer is 5-10 μm.

6. The method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery according to claim 5, characterized in that: The semi-curing orientation operation includes: First, raise the ambient temperature to 50-70°C, then introduce inert gas to form a semi-cured coating; Firstly, a horizontal shear force is applied to the semi-cured coating, and then a vertical magnetic field is applied to obtain a coating with directional arrangement of carbon fiber tubes; The coating with the carbon fiber tube directional arrangement is heated to 70-100° C., and a light source field is applied, and heated for 60-120 minutes to complete the semi-curing directional operation, wherein there are at least two light source points with different light intensities in the light source field.

7. The method for preparing a composite silicon-based negative electrode sheet for a solid-state lithium-ion battery according to claim 1, characterized in that: The step S1 comprises: S1.

1. Put the selected micron-sized silicon particles and nano-sized silicon particles into a stirring container at a mass ratio of 40-95:5-60, add a low-polarity solvent, and stir at 50-100 rpm for 60-120 min to obtain a premix, wherein the low-polarity solvent includes at least one of n-hexane, cyclohexane, and toluene, the particle size of the micron-sized silicon particles is 1-5 μm, and the particle size of the nano-sized silicon particles is 30-200 nm; S1.2, adding a cross-linking agent to the premix and performing ball milling mixing, wherein the cross-linking agent comprises at least one of hexamethylene diisocyanate, N,N'-methylenebisacrylamide, and triethylenetetramine, the ball milling mixing time is 60 to 360 min, the ball mill speed is 50 to 400 r / min, and the ball-to-material ratio is 1:1 to 10:1; S1.3, filtering or centrifuging the premix after ball milling, heating to 80-100° C. in a vacuum environment and drying for 240-360 min to obtain a composite silicon component.

Citation Information

Patent Citations

  • Silicon negative pole piece, preparation method thereof and lithium ion battery

    CN112542570A

  • Negative plate, preparation method thereof and lithium ion battery

    CN116154102A

  • Silicon negative electrode material for all-solid-state lithium ion battery as well as preparation method and application of silicon negative electrode material

    CN116417587A

  • Composite electrode material, method for manufacturing the same, composite electrode comprising the same and lithium-based battery comprising the said composite electrode

    US20200395607A1